If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+2X-6=6
We move all terms to the left:
X+2X-6-(6)=0
We add all the numbers together, and all the variables
3X-12=0
We move all terms containing X to the left, all other terms to the right
3X=12
X=12/3
X=4
| (6x)(12x)=(8)(9) | | -5+v/4=7 | | 100-97=x÷2 | | (4x+3)+(x+7)+80=180 | | 4(x+2)^2-12=0 | | 2z+-9=7 | | 10(x+1)=10+5 | | 6/1(x+6)=11 | | -6r-5=79 | | x^2+7-88=0 | | -14=-2+2d | | 104.5-18.5=x | | 10v+7=87 | | y=-300+2400 | | -3k+9=45 | | 4y+3=8y-7 | | X+2x+17=25 | | X=8-8y | | 25x-25=5x+75 | | x+6(x–1)=7(3+x) | | 16 | | (x+3)²)=-4(2x-7) | | 0=-5x^2-20x+7 | | (4x+3)*2+(x+7)*2=180 | | 5x-19=96 | | (4x+3)+(x+7)*2=180 | | `-2w=14+` | | ((4x+3)+(x+7))*2=180 | | 1/4z=6/27 | | 9x²-6x=11 | | –5.4d−8.67=1.33−4.4d | | (2x+5)(2x-1)=5 |